2017
DOI: 10.1016/j.wasman.2017.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Energy recovery from one- and two-stage anaerobic digestion of food waste

Abstract: One- and two-stage anaerobic digestion of food waste aimed at recovering methane (CH) and hydrogen and methane (H+CH), respectively, were compared in order to assess the potential benefits from the two-stage process in terms of overall energy recovery. Results suggest that a two-stage process where the first reactor is properly operated in order to achieve a significant net hydrogen production, may display a 20% comparatively higher energy recovery yield as a result, mainly, of enhanced methane production as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
67
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(79 citation statements)
references
References 47 publications
8
67
1
3
Order By: Relevance
“…Assays are assessed using a broad pH range (4.5-9.0 [15,21]), with the optimum found at 5.5 [11,13,14]. In this matter, the most adopted methods of controlling pH during batch trials are the use of an initial buffer solution [6,[13][14][15] or the automatic addition of an alkaline solution [19][20][21]. Temperature is set at mesophilic (35-39 • C) or thermophilic conditions (50-55 • C), according to the original conditions of the seed microorganisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assays are assessed using a broad pH range (4.5-9.0 [15,21]), with the optimum found at 5.5 [11,13,14]. In this matter, the most adopted methods of controlling pH during batch trials are the use of an initial buffer solution [6,[13][14][15] or the automatic addition of an alkaline solution [19][20][21]. Temperature is set at mesophilic (35-39 • C) or thermophilic conditions (50-55 • C), according to the original conditions of the seed microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…to avoid the presence of HCB [23][24][25][26][27][28][29]. Nevertheless, since in full scale digesters bacteria coexist in a wide range of species, and the fermentation of substrates into biohydrogen involves a wide consortium of microorganisms [30], the use of mixed cultures belonging to operative facilities is preferred by most authors [6,11,[13][14][15][16][17][18][19][20][21][31][32][33]. Moreover, using mixed-microorganism media is more functional and economically advantageous than using unique microbial populations.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of a substrate with a natural inhibitor, like citrus waste, the two-stage system offers another advantage by retaining part of the inhibitor in the first stage and secluding it from the second stage that contains the more sensitive methanogenic bacteria. A study by Gioannis et al [9], which utilized food waste for biogas production, supported this notion. It was shown that through a two-stage process, where the first reactor is properly operated in order to achieve a significant net hydrogen production, a 20% higher methane yield was obtained, compared to that of a single-stage process.…”
Section: Introductionmentioning
confidence: 92%
“…The first-order models known as the simplest model was applied to estimate the parameter, to improve the understanding of the biological process and predict the behaviour of the biological system in developing the anaerobic system [17]. The modified Gompertz model has been adopted to analyse the production of methane from batch experiments [18,19].…”
Section: Introductionmentioning
confidence: 99%